Catheter ablation of a latent accessory pathway under continuous infusion of adenosine: A case report. Issue 31 (31st July 2020) - Cismaru, Gabriel; Rosu, Radu; Puiu, Mihai; Gusetu, Gabriel; Istratoaie, Sabina; Cismaru, Andrei; Pop, Dana; Zdrenghea, Dumitru
Abstract: Rationale: In absence of conduction over the accessory pathway (AP) during the electrophysiological study, mapping and ablation is impossible. Various techniques can be used to activate absent conduction. In this presentation we describe the first case of latent AP ablation performed under continuous infusion of adenosine. Patient concerns: A 65-year-old man, presented to emergency department with atrial fibrillation and antegrade conduction through a left lateral AP. He had palpitations and lightheadedness that occurred every 2 to 3 weeks. Diagnosis: The electrophysiological study confirmed a latent left-side AP. Interventions: Catheter ablation could not be performed because of absent conduction through AP. Therefore, a continuous infusion of adenosine was used to activate AP. Ablation was performed at the left lateral mitral ring. Outcomes: After catheter ablation and a new adenosine bolus there was no conduction through AP. Lessons: In case of a latent AP when ablation is difficult to perform because of absent conduction at the time of electrophysiological study, adenosine can be used in doses of 1.5 mg/kg over 5 minutes continuous infusion.